Computational model for mammalian circadian oscillator: interacting with NAD+/SIRT1 pathway and age-related changes in gene expression of circadian oscillator - N. L. Podkolodnyy; N. N. Tverdokhleb; O. A. Podkolodnaya (Вавиловский журнал генетики и селекции)
Studies of the last decade reveal a new sight on the possible link between aging processes and circadian rhythm. New data on the role of the NAD+-dependent histone deacetylase SIRT1 in the integration of regulation pathways for circadian rhythms and metabolism as well as data on a new function of the NAD+ as the ”metabolic oscillator” open a promising direction in this area. In the paper we suggested a modification and extension of the most detailed model for the circadian oscillator developed by Kim and Forger (2012). We included the additional feedback of the oscillator which concerns genes/proteins NAMPT, SIRT1, and also NAM, NAD+. The regulation of transcription for gene NAMPT by transcription factor CLOCK/BMAL1 determine the appropriate rhythm of mRNA and protein NAMPT expression. Since an enzyme product of this gene is a key in the pathway of biosynthesis and recycling of NAD+, therefore the circadian rhythm is also characteristic for the fluctuations in the level of this coenzyme and in the activity of NAD+-dependent histone deacetylase SIRT1. The deacetylation of circadian oscillator components by this enzyme closes the feedback mediated through this pathway. In particular, the effects of SIRT1 in circadian oscillator are the gain of degradation of protein Per2, increasing of the gene Bmal1 transcription, deacetylation of chromatin in regulatory regions of circadian oscillator genes in the E-boxes area with subsequent suppression of transcription. We took into account all of these processes in our extended model of the circadian oscillator. Based on the experimental data on the aging changes in the activity of SIRT1 and the level of NAD+, we attempted to study the effect of these age-related changes on the functioning of the circadian oscillator. Simulation data showed a decrease in expression level of several genes of the circadian oscillator, in particular, Bmal1 and Per2, in the older age groups. In addition, our extended model predicted an increase in the period of oscillations. The results indicate that decrease in SIRT1 activity deal with agerelated NAD+ metabolic disorder may be one of the reasons for the circadian oscillator dysfunctions in the suprachiasmatic nuclei. Such disorders may result in a breaking of the circadian rhythms in the body as a whole.